Piezoelectric drive systems in ultraprecision machines: a review of the state-of-the-art. (5th May 2009) - Logan, D.; Ahearne, E.; Byrne, G.
The production of ultraprecision and micromachined components has been enabled by the development of a range of drive system technologies with commensurate resolution. In particular, systems based on piezoelectric actuators have provided an alternative to mechanical drive systems. These actuators have been incorporated in drive systems for high resolution positioning of atomic force microscopes, high frequency vibration compensation and high speed valves for diesel injection. The performance of systems based on piezo actuators is characterised by high electromechanical advantage, submillisecond response times and nanometric resolution. In many cases the inherent limited range of travel has been compensated by the design of flexure systems. When combined, these provide precision control free of friction and backlash, otherwise unattainable with conventional mechanical drives. The objective of this paper is to give an overview of the current state-of-the-art. It will highlight the novel application of these alternative technologies. The advantages of piezoelectric technology and their limitations will be discussed.